2015
DOI: 10.1128/aac.01303-15
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Decrease in Daptomycin Susceptibility in Clinical Staphylococcus aureus Isolates Associated with an Initial Mutation in rpoB and a Compensatory Inactivation of the clpX Gene

Abstract: dDaptomycin is a lipopeptide antibiotic used clinically for the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections. The emergence of daptomycin-nonsusceptible S. aureus isolates during therapy is often associated with multiple genetic changes; however, the relative contributions of these changes to resistance and other phenotypic changes usually remain unclear. The present study was undertaken to investigate this issue using a genetically characterized series of four isogenic clinical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…Here, we report that the mosaic penA alleles from two well-characterized ESC r clinical isolates, H041 (10) and F89 (12), reduce the fitness of N. gonorrhoeae both in vitro and in vivo. We hypothesized that mosaic penA alleles, while increasing ESC resistance, would impart a fitness deficit to a wild-type strain, but in nature, these resistant strains accumulate fitness-increasing mutations that allow the strains to spread (9,21,23,45), as has been shown for other antibiotic-resistant strains (46,47). We showed that FA19 penA41, but not FA19 penA89, acquired spontaneous compensatory mutations during coinfections in the female mouse model that markedly increased fitness.…”
Section: Discussionmentioning
confidence: 78%
“…Here, we report that the mosaic penA alleles from two well-characterized ESC r clinical isolates, H041 (10) and F89 (12), reduce the fitness of N. gonorrhoeae both in vitro and in vivo. We hypothesized that mosaic penA alleles, while increasing ESC resistance, would impart a fitness deficit to a wild-type strain, but in nature, these resistant strains accumulate fitness-increasing mutations that allow the strains to spread (9,21,23,45), as has been shown for other antibiotic-resistant strains (46,47). We showed that FA19 penA41, but not FA19 penA89, acquired spontaneous compensatory mutations during coinfections in the female mouse model that markedly increased fitness.…”
Section: Discussionmentioning
confidence: 78%
“…Further study showed that the rpoB-A477D allele modulates reduced susceptibility to daptomycin, vancomycin, and ␤-lactam antibiotics and contributes to a variety of pleiotropic effects, including modulation of Spx levels (61). Spx has been linked with both glycopeptide and ␤-lactam resistance in S. aureus in our own laboratory by virtue of the implication in drug resistance of its negative regulator yjbH (35) and an adaptor gene, trfA, that was shown to be Spx regulated (76).…”
Section: Discussionmentioning
confidence: 92%
“…Additional mutations associated with the DAP-R phenotype include genes encoding the RNA polymerase subunits rpoB and rpoC (Friedman et al 2006; Peleg et al 2012). A mutation in rpoB , resulting in the amino acid change A621E, was associated with increased expression of the dlt operon and correlated with an increase in positive cell surface charge, while RpoB mutations A621E and A477D were both linked to activation of cell wall biosynthesis and increased cell wall thickness (Cui et al 2010; Bæk et al 2015). …”
Section: Dap-r In Staphylococcus Aureusmentioning
confidence: 99%